Self-Management as a Substitute for Leadership: A Social Learning Theory Perspective - Manz, Charles C.; Sims, Henry P. (Academy of Management Review, 1980)
Kerr [1976] has coined the term “substitutes for leaders hip” in reference to nonleader sources of task structure and direction. We focus on one such substitute, the capability of the follower for self-management Individuals manage their own behaviors by setting personal standards, evaluating their performance in terms of these standards, and by self-administering consequences based on their self-evaluations. Specific techniques such as self-observation, goal specification, cueing strategies, incentive modification, and rehearsal can be used to exercise self-management behavior. Organizational leaders can help subordinates develop self-management skills.